Odpowiedzi

Najlepsza Odpowiedź!
2010-03-01T16:08:10+01:00
1.
-(x-0,4)(x+0,4)+(x-0,4)²=-0,08
-(x²+0,4x-0,4x-0,16)+x²-0,8x+0,16=-0,08
-x²-0,4x+0,4x+0,16+x²-0,8x+0,16=-0,08
-0,8x=-0,4
x=-0,4:(-0,8)
x=1/2
2.
3(x+2)²+(2x-1)²-7(x+3)(x-3)=28
3(x²+4x+4)+(4x²-4x+1)-7(x²-3x+3x-9)=28
3x²+12x+12+4x²-4x+1-7x²+21x-21x+63=28
8x=-48
x=-6
3.
5(x+3)²-5(x-4)(x+4)+12=77
5(x²+6x+9)-5(x²+4x-4x-16)+12=77
5x²+30x+45-5x²-20x+20x+80+12=77
30x=-60
x=-2
4.
(2y-1)(2y+1)-(2y-3)²+12y=38
4y²+2y-2y-1-(4y²-12y+9)+12y=38
4y²+2y-2y-1-4y²+12y-9+12y=38
24y=48
y=2